Determining Chronic Cough Using the Methacholine Bronchial Provocation Test - Aksu, Esra Arslan; Uzun, Oğuz (Jurnal Respirasi, 2025)
Introduction: Chronic cough is a common symptom in pulmonology outpatient clinics, often associated with lung conditions, though extrapulmonary causes can also be responsible. This study aimed to detect bronchial hyperreactivity (BHR) and cough-variant asthma using a methacholine bronchial provocation test (BPT) in patients with chronic cough for whom standard diagnostic procedures could not identify a cause. Methods: This prospective study evaluated patients admitted to the clinic who presented with chronic coughs over one year. A BPT was performed on patients for whom standard diagnostic procedures failed to identify a cause, and this selected group was included in this study. Results: This study included a total of 40 patients who were examined for chronic cough symptoms without an identifiable etiology. The BPT was negative (PD20 >16 mg/mL) in 30 patients (75%) and positive in 10 patients (25%). Among the patients with negative BPT results, 13 (43.3%) had no identifiable cause for their cough. Conclusion: This study differs from others by focusing on a selected group of patients with chronic coughs for whom the etiology could not be determined through standard diagnostic procedures. The BPT was performed alongside typical diagnostic tests, and no diagnoses were made in the included patients. Tests identified BHR and cough-variant asthma in 25% of these patients, suggesting that BPT is a valuable tool in diagnosing chronic cough when conventional methods fail.